Effects of Er: YAG laser and acid etching on bond strength of clear aligner attachments to fluorotic enamel - Rui Xia; Jie Lei; Maoxuan Luo; Yao Xiao (PLoS ONE, 2025)
Background There is a lack of research on the bonding ability of attachments to fluorosis enamel. This study evaluates Er: YAG laser-assisted acid etching as a potential optimization protocol. Methods Twenty healthy teeth and ninety fluorotic teeth (Thylstrup-Fejerskov Index = 4) were divided into a control group (healthy enamel + acid etching) and a fluorotic group (acid etching 30/60/90 seconds vs. Er: YAG laser + acid etching). The enamel surface was analyzed using scanning electron microscopy, and the shear bond strength (SBS) of each group (n = 10/group) was tested. Results Attachments exhibited higher SBS than brackets (P < 0.01). Laser-acid etching enhanced SBS compared to acid etching alone (P < 0.01). Laser-treated surfaces exhibited predominantly mixed fracture and resin cohesion fractures, in contrast to adhesive interface fractures and mixed fractures in the acid-only groups. Conclusion Er: YAG laser (100mJ/30 Hz) with 60 seconds acid etching achieves excellent bonding for fluorotic enamel attachments, restoring adhesion to healthy enamel levels while preventing over-etching damage. This protocol shows clinical potential for bonding fluorotic enamel.